Pathophysiology of leprosy: immunological response related to clinical forms - Yonemoto, Ana Cláudia Ferreira (2022)
The aim of this study is to elucidate the physiopathology of leprosy and relate it to its clinical forms through an narrative review. The search for articles was carried out in the LILACS, PUBMED, SCIELO, MEDLINE and VHL databases, and the following descriptors were used: Leprosy, Mycobacterium leprae, physiopathology and leprosy reaction. The search was restricted to studies published from 2013 until the year 2021, and articles related to the theme were selected. Leprosy presents a complex pathophysiology, correlated with different immune patterns, involving dendritic cells, pattern recognition receptors (PRRs), macrophages and natural killer (NK) cells, which will release interleukins that will determine the type of immune response of the host, among which we address Th1, Th2, Th17, T regulators (Treg), Th9, Th22 and others. When the cellular immune pattern is activated with a predominance of the Th1 pattern, the patient tends to progress to the benign pole (tuberculoid leprosy), if the specific cellular response is mild or absent to the antigens of the same agent, with a prevalence of the Th2 pattern and humoral response, the individual tends to the malignant pole (lepromatous leprosy) of the disease, as well as to the development of type 1 and type 2 leprosy reactions.